2018
DOI: 10.1002/ecs2.2145
|View full text |Cite
|
Sign up to set email alerts
|

Plant community change in three Mongolian steppe ecosystems 1994–2013: applications to state‐and‐transition models

Abstract: Citation: Jamiyansharav, K., M. E. Fern andez-Gim enez, J. P. Angerer, B. Yadamsuren, and Z. Dash. 2018. Plant community change in three Mongolian steppe ecosystems 1994-2013: applications to state-and-transition models.Ecosphere 9(3):e02145. 10.1002/ecs2.2145Abstract. Interacting effects of climate change and livestock grazing on semi-arid grassland ecosystems have not been well studied, especially on a long-term basis. This paper analyzes changes in plant community composition in relation to grazing intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
2
15
1
Order By: Relevance
“…In the ST, ordination analysis showed that plant community composition is associated most strongly with growing‐season precipitation and moderately associated with livestock use, similar to findings of Jamiyansharav et al. (). As in the DS, herders’ assessment scores correlated with the axis 1 and herders tended to give higher scores to Stipa krylovii dominated plots.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the ST, ordination analysis showed that plant community composition is associated most strongly with growing‐season precipitation and moderately associated with livestock use, similar to findings of Jamiyansharav et al. (). As in the DS, herders’ assessment scores correlated with the axis 1 and herders tended to give higher scores to Stipa krylovii dominated plots.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding aligns with other TEK studies conducted in this mesic and more productive zone of Mongolia, where herders also identified heavy grazing is the primary factor influencing rangeland degradation (Kakinuma et al 2008, Bruegger et al 2014. Herder observations in our study and others are consistent with scientific observations that livestock grazing has a strong effect on rangeland condition in this zone (Fernandez-Gimenez and Allen-Diaz 2001, Van Staalduinen et al 2007, Jamiyansharav et al 2018.…”
Section: Perceived Causes Of Rangeland Health and Degradation Relatisupporting
confidence: 92%
See 2 more Smart Citations
“…A growing body of evidence from observational studies of longterm monitoring plots, remotely sensed data, or species range shifts demonstrates that vegetation distribution is responding strongly to environmental change (Doughty et al, 2016;Franklin, Serra-Diaz, Syphard, & Regan, 2016;Jamiyansharav, Fernández-Giménez, Angerer, Yadamsuren, & Dash, 2018;Maguire, Nieto-Lugilde, Fitzpatrick, Williams, & Blois, 2015;Parmesan & Yohe, 2003;Schuster, Martinez, & Dukes, 2014;Simkin et al, 2016). While these studies capture ongoing responses to environmental change, attribution to a particular cause can be difficult (Cudlin et al, 2017), thereby complicating comparisons to manipulative studies.…”
mentioning
confidence: 99%